Meningkatkan Minat Belajar Siswa pada Pembelajaran Matematika Kelas V di SDN 31 Mataram - Triana, Dita; Tahir, Muhammad; Suciani, Baiq Ria (Mataram University, 2025)
This study aims to improve the interest and learning outcomes of fifth-grade students at SDN 31 Mataram in mathematics through the implementation of the Problem-Based Learning (PBL) model supported by the interactive learning media Wordwall. The research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of the stages of planning, implementation, observation, and reflection. The subjects of this study were fifth-grade students. Data were collected through observation and tests. The results showed a significant improvement in students’ learning outcomes, with the average score increasing from 69.7 in the pre-cycle to 91.6 after the intervention. Furthermore, students demonstrated higher enthusiasm and active participation during the learning process. Wordwall proved to be effective in motivating students and enhancing conceptual understanding through engaging interactive activities. These findings indicate that the combination of PBL and interactive media such as Wordwall can create an inclusive and engaging learning environment, overcome challenges in mathematics learning, and improve students’ academic achievement.